Review on the textbook “Fundamentals of ecology”: textbook for students of higher educational institutions / [V.G. Bardov, V.I. Fedorenko, E.M. Biletska et al.]; under edition of V.G. Bardov, V.I. Fedorenko. – Vinnytsya: Nova Knyha, 2013. – 424 p. - Shmatkov, H. H. (Medicni Perspektivi, 2014)
Review on the textbook “Fundamentals of ecology”: textbook for students of higher educational institutions / [V.G. Bardov, V.I. Fedorenko, E.M. Biletska et al.]; under edition of V.G. Bardov, V.I. Fedorenko. – Vinnytsya: Nova Knyha, 2013. – 424 p.